Fuzzy logic-based algorithm resource scheduling for improving the reliability of cloud computing - Zavvar, Mohammad; Rezaei, Meysam; Garavand, Shole; Ramezani, Farhad (Penerbit Universiti Kebangsaan Malaysia, 2016)
Cloud computing is an important infrastructure for distributed systems with the main objective of reducing the use of resources. In a cloud environment, users may face thousands of resources to run each task. However, allocation of resources to tasks by the user is an impossible endeavor. Accurate scheduling of system resources results in their optimal use as well as an increase in the reliability of cloud computing. This study designed a system based on fuzzy logic and followed by an introduction of an efficient and precise algorithm for scheduling resources for improving the reliability of cloud computing. Waiting and turnaround times of the proposed method were compared to those of previous works. In the proposed method, the waiting time is equal to 26.99 and the turnaround time is equal to 82.99. According to the results, the proposed method outperforms other methods in terms of waiting time and turnaround time as well as accuracy.